Rapidly cell-penetrating and reductive milieu-responsive nanoaggregates assembled from an amphiphilic folate-camptothecin prodrug for enhanced drug delivery and controlled release. (6th January 2017) - Xu, Zhigang; Hou, Meili; Shi, Xiaoxiao; Gao, Yong-E.; Xue, Peng; Liu, Shiying; Kang, Yuejun
Abstract : Self-assembled small molecular prodrug loaded with camptothecin in response to glutathione and folate receptors for combined tumour detection and treatment. Abstract : Accurate diagnosis and treatment based on small molecular prodrugs can enhance drug efficiency and reduce side-effects during cancer therapy. Herein, we report the preparation of a type of glutathione (GSH)-responsive small prodrug delivery system based on targeting folic acid (FA) and conjugating with the hydrophobic antitumor drug camptothecin (CPT) via disulfide bonds. The obtained prodrug is capable of high and precise drug loading (36.8 wt%) and can self-assemble into nanoaggregates with an average size of 46.4 nm in an aqueous solution. The GSH-triggered release of CPT can reach a maximum of 82% under 10 mM GSH in 60 h, which is dramatically higher than 12% of CPT released in a physiological environment. More interestingly, the resulting prodrug can also work as a "switchable" fluorescence probe, which exhibits fluorescence changes in response to GSH stimulus or FA receptors on the membranes of tumor cells. Specifically, the fluorescence of the prodrug is quenched in the physiological environments, whereas strong fluorescence is activated in the tumoral microenvironment expressing high levels of GSH or when the FA terminal is conjugated with the receptors on the membranes of tumor cells. Furthermore, the FA-CPT prodrug shows a superior specificity and higher cytotoxicity for FA receptor-positive KB tumor cells as compared to those of FA receptor-negative A549 tumor cells. Therefore, we believe that this FA-CPT prodrug can be used for the recognition and diagnosis of tumor cells and it also provides a promising modality towards an effective cancer therapy.